Comparing the electronic relaxation dynamics of aniline and d7-aniline following excitation at 272–238 nm1. Issue 25 (7th July 2015) - Kirkby, Oliver M.; Sala, Matthieu; Balerdi, Garikoitz; de Nalda, Rebeca; Bañares, Luis; Guérin, Stéphane; Fielding, Helen H.
<x xml:space="preserve">Abstract</x> Femtosecond studies of electronic relaxation in aniline reveal evidence for a 3-state conical intersection and show that tunnelling is unimportant.